2023
DOI: 10.24815/siele.v10i1.26021
|View full text |Cite
|
Sign up to set email alerts
|

Group work in Zoom breakout rooms to enhance English-speaking self-efficacy for active learning activities

Abstract: The study aimed at analyzing the effectiveness of assigning students to work in groups using Zoom breakout rooms to enhance their speaking self-efficacy to participate in active learning activities in an online learning context. Thirty-six students of Diploma 3 of the Accounting Program attending English for Accounting course were purposively selected as the respondents of the study. The data were collected using a three-part questionnaire distributed electronically using Google Forms. The validity and reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…It was found that PEOU and PU truly represent variables that are favourably connected with and stimulate students' BI and AU of Zoom as an alternative educational platform in learning knowledge-skill-based concepts in a variety of PE courses. As a result, the findings suggested that the implementation of the aforementioned videoconferencing platform was incontestably uncomplicated and simple to use, consistent with the findings of previous inspections (Hartono et al, 2023;Hidayat et al, 2022). Students' optimistic views of Zoom as a useful platform have the potential to boost their overall academic performance because of its accessibility and practicability.…”
Section: Assessment Of Structural Modelsupporting
confidence: 82%
See 1 more Smart Citation
“…It was found that PEOU and PU truly represent variables that are favourably connected with and stimulate students' BI and AU of Zoom as an alternative educational platform in learning knowledge-skill-based concepts in a variety of PE courses. As a result, the findings suggested that the implementation of the aforementioned videoconferencing platform was incontestably uncomplicated and simple to use, consistent with the findings of previous inspections (Hartono et al, 2023;Hidayat et al, 2022). Students' optimistic views of Zoom as a useful platform have the potential to boost their overall academic performance because of its accessibility and practicability.…”
Section: Assessment Of Structural Modelsupporting
confidence: 82%
“…Zoom is used by universities and colleges across the world because of its adaptability and ease of use, both of which benefit students. For instance, the newly published paper by Hartono et al (2023) has revealed that the students felt more confident in their ability to communicate in English because they had more chances to practise, as well as gain exposure to, the language; they received persuasive support in the form of positive reinforcement from their peers and they encountered less anxiety when doing so. Therefore, students' opportunities to actively study and improve their English-speaking self-efficacy were fostered through group work in Zoom breakout rooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This phenomenon affected the education system regarding curriculum, methods, lecturer roles, student positions, and assessment. Many students experienced learning fatigue (Ebner & Greenberg, 2020;Hartono et al, 2023) and low attendance and engagement (Hollister et al, 2022;Ubu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%